The effect of aqueous extract of the roots of Salep plants on the serum concentration of progesterone and LH hormone in female rats - kavous solhjo; hossein Kargar jahromi; keramat allah solhjo; zahra Kargar jahromi; zahra Khabbaz Kherameh; Maryam Mediyar (فصلنامه دانشگاه علوم پزشکی جهرم, 2015)
Background: Using the Salep as an energetic drug and sexual stamina enhancer is common in traditional medicine. This study aims to investigate the effect of aqueous extract of Salep on serum level of progesterone and LH hormones in the female rats. Materials and Methods: In this experimental study, 40 adult female Wistar rats were selected and randomly divided into 5 groups: control (no drug), sham (which received 1 ml distilled water), the experimental group 1 (recipient of 20 mg / kg aqueous extract of Salep), the experimental group 2 (recipient of 40 mg / kg aqueous extract of Salep) and experimental group 3 (recipient of 80 mg / kg aqueous extract of Salep). In the experimental groups the extract was injected intraperitoneally for 28 days. At the end of the experimental term, the mice were bled to examine the serum level of the progesterone and LH hormones (p<0.05). Findings: Injecting the aqueous extract of Salep caused a significant increase in the serum level of progesterone and LH hormones compared to control group (p <0.05). Conclusion: The aqueous extract of Salep can play a positive role in the process of ovulation in females, through increasing the serum levels of progesterone and LH hormones. Key Word : Salep, Progesterone, LH, Female Rats.